2018
DOI: 10.1186/s12886-018-0830-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in anterior chamber volume after implantation of posterior chamber phakic intraocular lens in high myopia

Abstract: BackgroundThe present study aimed to assess changes in, and the factors that influence, anterior chamber volume (ACV) after implantable contact lens (ICL) implantation in high myopia eyes using a Pentacam.MethodsThe study sampled 26 high myopia patients (45 eyes) who were treated with ICL implantation. These patients were followed for an average of 4.28 months postoperatively. ACV was measured with a Pentacam preoperatively and at 3 months postoperatively. The data were analyzed by paired samples Wilcoxon sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…17 It has been proved to be an important factor related to the clinical vault after surgery; in previous studies, Zhu et al reported a nearly 40% of decreased ACV after surgery. 6,18 They also found a significant positive correlation between the preoperative and postoperative ACV. Consistent with their reports, Takagi et al selected the preoperative ACV as an important variable to establish the prediction formula of postoperative ACV.…”
Section: Discussionmentioning
confidence: 85%
“…17 It has been proved to be an important factor related to the clinical vault after surgery; in previous studies, Zhu et al reported a nearly 40% of decreased ACV after surgery. 6,18 They also found a significant positive correlation between the preoperative and postoperative ACV. Consistent with their reports, Takagi et al selected the preoperative ACV as an important variable to establish the prediction formula of postoperative ACV.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study used Scheimpflug-based tomography (Pentacam, Oculus, Arlington, WA) for the prediction equation to calculate the postoperative ACV [11]. The authors reported that the postoperative ACV is correlated with the postoperative vault, preoperative ACV, ACD, and horizontal ACA and can also be predicted by these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report showed that intraocular pressure (IOP) was elevated by angle closure after ICL implantation [10]. ACV measured by anterior segment optical coherence tomography (AS-OCT) was useful for observing the change of anterior segment and angle structure after ICL implantation [11]. Based on these studies, we presumed that ACV would be useful for predicting the anterior chamber angle after ICL implantation.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…evaluated the AC volume (ACV) (Pentacam imaging) after ICL implantation in 45 eyes of 26 patients with high myopia preoperatively and postoperatively over a mean follow-up period of 4.28 months. [ 16 ] The mean ACV was found to decrease significantly (a decrease of 40%) from 198.33 ± 33.08 mm 3 before surgery to 118.65 ± 17.70 mm 3 after surgery. They found a positive correlation between postoperative ACV and ACA and concluded the ACV to be a sensitive parameter that is complementary to vault and ACD in preoperative assessment and postoperative monitoring of ICL patients.…”
Section: Discussionmentioning
confidence: 99%